Evaluation Of Low-Densitypolyethylene Degradation By Bacillusval Lismortis (Journal of Pharmaceutical Negative Results, 2023)
The environment is seriously threatened by the build-up of resistant polymers, one of the mostcommon plastics that are released into the environment is polyethylene. The study investigatesways to speed up polyethylene's biodegradation. Bacteria isolated from Visakhapatnam pollutionsites were employed to degradation of 75µ and 50µ LDPE films. The maximum protein contentforVB1was0.79g/Lwiththemaximumhydrophobicityof17.16%of50µLDPEfilms.Byusing16S rRNA gene sequencing, Bacillus vallismortis was found as a potential LDPE-degradingbacterial strain. Using batch fermentation under aerobic circumstances, the degrading capabilityof B. vallismortis has been examined under various operational conditions. The ideal conditionsfor LDPE deterioration were discovered by using the preliminary optimization by one factor at atime technique. the optimal conditions for LDPE degradation byB. vallismortis were 37°Ctemperature, pH 7, 80 days of incubation time, and 0.03 mmol/L of FeCl2, 0.75g/L of KNO3, 2.0g/Lofstarch and0.75g/Lof ethanol.Attheseoptimumconditions,maximumLDPEdegradationwas33.79% and29.42%with dissolvedCO2of1.73 g/L &1.06g/L for50μ & 75μ LDPE films.